The Massachusetts state constitution - Friedman, Lawrence, 1967-; Thody, Lynnea; Massachusetts (Oxford ; New York : Oxford University Press, 2011)
The Massachusettes Constitution is the oldest state constitution and has remained essentially unchanged since it was drafted in 1780. It served as a model for the US Constitution and many of the state constitutions that followed. The book provides an outstanding constitutional and historical account of the state's governing charter. It begins with an overview of the constitutional history, and then provides an in-depth, section-by-section analysis of the entire constitution, detailing important changes that have been made since its drafting.
The constitutional history of Massachusetts -- Massachusetts Constitution and commentary.
Includes bibliographical references (pages 213-223) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Constitutions -- Massachusetts; Constitutional law -- Massachusetts; Constitutional history -- Massachusetts; Constitutions -- Massachusetts; Droit constitutionnel -- Massachusetts; Histoire constitutionnelle -- Massachusetts; LAW -- Constitutional; LAW -- Public; Constitutional history; Constitutional law; Constitutions; Massachusetts; constitutions; Constitutions; Constitutions; Constitutions